Social inequality in the association between life transitions into adulthood and depressed mood: a 27-year longitudinal study - Jørgensen, Magnus; Smith, Otto R. F.; Wold, Bente; Haug, Ellen (Frontiers in Public Health, 2024)
Background: Few studies have considered the life-course development of depressive symptoms in relation to life transitions in early-adulthood and whether these might affect depressive trajectories differently depending on specific indicators of parental socioeconomic status (SES). In the present work, we explore these questions using the adolescent pathway model as a guiding framework to test socially differential exposure, tracking and vulnerability of the effects of life transitions on depressed mood across different socioeconomic backgrounds. Methods: Latent growth modelling was used to estimate the associations between indicators of parental SES (parental education and household income) and depressed mood from age 13 to 40 with life transitions (leaving the parental home, leaving the educational system, beginning cohabitation, attaining employment) as pathways between the two. Our analyses were based on a 27-year longitudinal dataset (n = 1242) of a Norwegian cohort with ten time points in total. To make socioeconomic comparisons, three groups (low, mid, and high) were made for parental education and income respectively. Results: Depressed mood decreased from age 13 to 40. The low and high parental education groups showed a stable difference in depressed mood during early adolescence which decreased in young adulthood and then increased slightly in mid-adulthood. The low household income group showed higher depressed mood across young adulthood compared to the medium and higher household income group. For life transitions, leaving the parental home and beginning cohabitation was associated with an added downturn of the trajectory of depressed mood when adjusting for other transitions. However, adolescents with high parental education showed a relatively stronger decrease in depressed mood when leaving the parental home. Similarly, adolescents with a high household income showed a relatively stronger decrease in depressed mood when leaving the educational system. Conclusions: Depressed mood decreased over time and developed differently depending on parental education and household income. Life transitions were generally associated with reductions in depressed mood across time, but lower SES youths were not found to be more socially vulnerable to the effects of these.